PENGARUH SERTIFIKASI HALAL TERHADAP MINAT KONSUMSI MAKANAN PRODUK AICIRO DI KOTA MALANG - Chofifah Wachid; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2022)
This study aims to determine the effect of Halal Certification to Interest in Food ConsumptionAiciro Product in Malang City. This type of research is correlational quantitative research. In thisstudy the samples taken were Malang City Community and Malang City Community who haveconsumed Aiciro product with the number 35 people. Taking the number of samples using theNon Probability technique Sampling with Purposive Approach Sampling to obtain respondent. .The analysis tool used is a simple linear regression analysis using SPSS. The results showed thatthe sig value was 0.009 <0.05 means that Ho is rejected and Ha is accepted. This means that thehalal credential of the independent variable has a partial positive and significant impact on theinterest consumption options of the dependent variable. This means that the presence of halalcertification can influence Aichiro's interest in food consumption in the city of Malang.